Impacto do Diabetes Mellitus tipo 2 nos desfechos desfavoráveis de pacientes hospitalizados por COVID-19 - Aguilar, Rodrigo Santos (2023)
Background: Diabetes mellitus-2 (DM-2) is as an important risk factor for complications and death in COVID-19 patients. The real impact of diabetes on the total length of hospital stay and in intensive care is not yet well established in the literature. The aim of this study was to investigate the real impact of DM-2 on the length of intensive care unit (ICU) stay and clinical outcomes of COVID-19 hospitalized patients. Methods: Prospective cohort study in 214 consecutive hospitalized patients due to COVID-19 divided in 55 Diabete-Mellitus-2 (DM) and 159 non-Diabetic (ND) patients. They underwent clinical evaluation, laboratory tests on hospital admission and they were followed-up in order to investigate clinical outcomes, such as: length of stay in the hospital, necessity for and length of stay in the ICU and/or death. Results: Diabetic patients had a prolonged length stay in ICU compared to ND (16[7-24]; 6[6-12]; p=0.01, respectively), with no difference in total length of stay in the hospital (p=0.41) and death between groups (p= 0.41). There was a significant difference in Kaplan-Meyer curves considering the presence of DM-2, adjusted for age, considering the length of stay in the ICU. (HR=1.7; CI:1.03-2.81; p=0.01). Conclusion: The presence of DM-2 was considered a predictor of prolonged length of stay in ICU in COVID-19 patients. Individualized strategies should be implemented in these patients to minimize clinical outcomes.